The international transmission of monetary policy in a dollar pricing model - Juha Tervala (Bank of Finland, 2007)
This paper analyses the international transmission of monetary policy in a case where all export prices are set in US dollars. 'Dollar pricing' implies that the international effects of US monetary shocks are different to those of European shocks because of asymmetric exchange rate pass-through to import prices. A dollar pricing model can explain the observed asymmetry in the transmission of monetary policy: US monetary policy affects US output more than European monetary policy affects European output. I also show that the dollar pricing model reintroduces the current account as an important channel through which monetary policy affects welfare in the short run. The paper concludes that under dollar pricing monetary expansion is a beggar-thy-neighbour policy.
URN:NBN:fi:bof-20140807395
Keywords: F41; F42; F30; 330; open economy macroeconomics; monetary policy; international policy transmission